2010
DOI: 10.1210/jc.2009-2387
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Metabolic Effects of Prompt Surgical Treatment in Patients with an Adrenal Incidentaloma Causing Biochemical Hypercortisolism

Abstract: Regarding the various components of the metabolic syndrome, in patients with adrenal incidentalomas and SH, surgery is beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
145
0
6

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(161 citation statements)
references
References 34 publications
5
145
0
6
Order By: Relevance
“…In addition, patients with intermittent cortisol secretion may present with adverse effects; however, they can have normal adrenal function at a single evaluation. This is a plausible explanation for the improvement in arterial hypertension, type 2 diabetes, and insulin sensitivity after adrenalectomy, reported in adrenal incidentaloma patients with (7,8,29,30,31,32) and without SCS (8,31,32). This might also be the case for transient adrenal insufficiency after adrenalectomy, considered as an indirect proof of cortisol hypersecretion, described in patients with and without SCS (8,32).…”
Section: European Journal Of Endocrinologymentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, patients with intermittent cortisol secretion may present with adverse effects; however, they can have normal adrenal function at a single evaluation. This is a plausible explanation for the improvement in arterial hypertension, type 2 diabetes, and insulin sensitivity after adrenalectomy, reported in adrenal incidentaloma patients with (7,8,29,30,31,32) and without SCS (8,31,32). This might also be the case for transient adrenal insufficiency after adrenalectomy, considered as an indirect proof of cortisol hypersecretion, described in patients with and without SCS (8,32).…”
Section: European Journal Of Endocrinologymentioning
confidence: 74%
“…This is a plausible explanation for the improvement in arterial hypertension, type 2 diabetes, and insulin sensitivity after adrenalectomy, reported in adrenal incidentaloma patients with (7,8,29,30,31,32) and without SCS (8,31,32). This might also be the case for transient adrenal insufficiency after adrenalectomy, considered as an indirect proof of cortisol hypersecretion, described in patients with and without SCS (8,32). It should also be noted that morbidities considered as adverse effects of subtle cortisol hypersecretion are not specific for cortisol excess and have an increased prevalence in the general population, especially over the sixth decade of life, when adrenal incidentalomas are more frequently detected.…”
Section: European Journal Of Endocrinologymentioning
confidence: 80%
“…It is reported in the 5-30% of patients with AI, accordingly to the various diagnostic criteria used in the literature (8,9,10). In patients with BAI, the prevalence of SH has been reported to be even higher, in relation to the tumour size (11).…”
Section: Introductionmentioning
confidence: 96%
“…As widely accepted guidelines on this topic were not available, pituitary hypercortisolism was diagnosed in patients who presented abnormal DST, AH, together with at least one of the following two alterations: i) urinary free cortisol (UFC) levels O193 nmol/24 h (normal values nmol/24 h), which is the cutoff of both our own and international normal reference values (6,13) in at least two measurements; ii) high midnight serum or salivary cortisol levels (awake value, cutoff 207 and 2.8 nmol/l respectively).…”
Section: Subjectsmentioning
confidence: 99%
“…Recent studies have demonstrated a high prevalence (5-30%) of SH (defined as a condition of biochemical cortisol excess without the classical signs or symptoms of overt hypercortisolism) in patients with adrenal incidentalomas (5,6,7). Interestingly, these patients showed long-term complications of cortisol excess, such as hypertension, insulin resistance, type 2 diabetes, central obesity, dyslipidemia, and an increased risk of osteoporosis and vertebral fractures, that partially reverted by adrenalectomy (8,9,10,11).…”
Section: Introductionmentioning
confidence: 99%